THE INFLUENCE OF PERFORMANCE MEASUREMENT SYSTEM ON THE IMPLEMENTATION OF SAKIP IN THE JAMBI PROVINCIAL GOVERNMENT - Muhammad Gowon; Yuliusman Yuliusman; Fortunasari Fortunasari (UNIB Press, 2021)
Performance Measurement System (PMS) including Performance Accountability is the obligation of every institution to be implemented accurately and measurably. Government AgencAy Performance Accountability System (SAKIP) which has been regulated in PP no. 29 of 2014 contains regulations of the President of the Republic of Indonesia regarding general regulations for the implementation of SAKIP. The purpose of this study was to determine the effect of the PMS factors on the implementation of SAKIP in the Jambi provincial government by connecting the 5 factors of the PMS and the implementation of SAKIP that influenced them. Specifically, the objects or parts of local government organizations that can explain this problem are the existing agencies, agencies and bureaus or regional apparatus organizations that are under the auspices of the provincial government. The research method used is descriptive quantitative. The warp Partial Least Square (warpPLS) program is a variance-based data processing program created to solve the problems caused by covariance-based SEM. This study hypothesizes the influence of the PMS factors on the implementation of SAKIP. The activities carried out began with submitting proposals to the Jambi provincial government, which then sought data directly or through third parties. Students as enumerators are used to search for data in the field. Primary data used comes from provincial government officials, while secondary data is obtained using the services of parties who are not directly involved with Jambi provincial government policies. The research was conducted by directly observing the Jambi governor's office and was also carried out using only information technology via the internet network. So that the information obtained does come from data sources that are truly valid, reliable and trustworthy.